Innate Immunity of Neonates and Infants - Yu, Jack C.; Khodadadi, Hesam; Malik, Aneeq; Davidson, Brea; Salles, Évila da Silva Lopes; Bhatia, Jatinder; Hale, Vanessa L.; Baban, Babak (Frontiers in Immunology, 2018)
Many important events occur at birth. The fetus is suddenly removed from a protected intra-uterine environment that is aquatic, warm, and nearly sterile, to the dry, cold external world laden with microbes. From this external environment, it must obtain nutrients and oxygen; and to that external environment, it expels metabolic wastes, with trillions of other organisms competing with it to do the same. This is the biotic process that exposes the neonate to an ecosystem in which it is a heterotrophic member. For microbial organisms in that same environment, the neonate is a both an ideal living space and a good source of food. To survive, the neonate must interact with many organisms, making use of some, while vigorously defending against the others like a nation conducting trade with friendly countries while guarding against hostile ones from invading it, waging wars if necessary. The neonatal immune system is tolerant to self, permits interactions with beneficial microbes, and provides defense against the harmful microbes. This review draws analogy from a national defense perspective because of the great similarities between that and the immune system in terms of function, needs, and limitations. Both are essential and potentially dangerous. Both require training, resources, maintenance, intermittent reactive expansion, judicious deployment, and demobilization. We will provide the known biological counterparts of all five core operational elements, the five Ds of defense -- detection, discrimination, deployment, destruction, de-escalation, with special focus on innate immunity, maternal support and influence during the neonatal and infancy periods.